Exploring the Techniques of Creating Images Utilized by Sylvia Plath in her Poetry - Ali , Ayad Hammad; Ayyed , Omar Saadoon (Dirasat: Human and Social Sciences, 2023)
Objectives: This research aims to understand the methods employed by Sylvia Plath in crafting metaphorical images. Another objective is to analyze these metaphorical images through the conceptual metaphor theory. The study assumes that Sylvia Plath relies on specific concepts derived from her personal pains and discouraging life experiences in the composition of her figurative images. Methods: Lakoff and Johnson’s (1980) model has been adopted with some requisite modifications to analyze twelve randomly selected poems from Sylvia Plath’s collection. The analysis methods involve decoding figurative images based on three elements of implicit meaning perception that underlie each metaphorical image. Results: The results revealed that Plath adopted seven methods shaped by specific elements such as metaphorical forms, body parts, colors, and natural elements, which assisted the poet in creating her distinctive figurative images. It was also confirmed that the conceptual metaphor theory was highly effective in analyzing the metaphorical images employed by the poet. Conclusion: The poet constructed her images by relying on two mechanisms, using various linguistic patterns, and blending disparate elements together to depict a specific concept. This made her poetry more effective and eloquent.